2016
DOI: 10.1021/jacs.6b03215
|View full text |Cite
|
Sign up to set email alerts
|

Tri(1-adamantyl)phosphine: Expanding the Boundary of Electron-Releasing Character Available to Organophosphorus Compounds

Abstract: We report here the remarkable properties of PAd3, a crystalline air-stable solid accessible through a scalable SN1 reaction. Spectroscopic data reveal that PAd3, benefiting from the polarizability inherent to large hydrocarbyl groups, exhibits unexpected electron releasing character that exceeds other alkylphosphines and falls within a range dominated by N-heterocyclic carbenes. Dramatic effects in catalysis are also enabled by PAd3 during Suzuki-Miyaura cross-coupling of chloro(hetero)arenes (40 examples) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
161
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(175 citation statements)
references
References 69 publications
(45 reference statements)
6
161
0
4
Order By: Relevance
“…2c); these lower e.r. might partly arise from an increase in attractive London dispersion forces between the 3,5-bis-(2,4,6-( i -Pr) 3 -phenyl)phenyl group and the substrate’s alkyl chain 45,46,47 . It is however more plausible that higher conformational mobility of the alkyl chains disrupt N→Na chelation [less optimal C NHC -Cu-C 1 -C 2 dihedral angle in I (151.3°) vs. in I (131.8°)].…”
Section: Resultsmentioning
confidence: 99%
“…2c); these lower e.r. might partly arise from an increase in attractive London dispersion forces between the 3,5-bis-(2,4,6-( i -Pr) 3 -phenyl)phenyl group and the substrate’s alkyl chain 45,46,47 . It is however more plausible that higher conformational mobility of the alkyl chains disrupt N→Na chelation [less optimal C NHC -Cu-C 1 -C 2 dihedral angle in I (151.3°) vs. in I (131.8°)].…”
Section: Resultsmentioning
confidence: 99%
“…One of the main reasons for their broad range of applications is the intriguing ease with which the steric and electronic properties of phosphines can be rationally tuned using various substituents . Although a huge variety of phosphines with diverse stereoelectronic properties have been synthesized over the last decades, the limit of electron‐donating character accessible to phosphines has been defined by alkylphosphines for more than half a century and modest advancement in this respect has been achieved using electropositive plumbyl, carboranyl, N‐heterocyclic boryl, anionic boratabenzene, or adamantyl substituents.…”
Section: Figurementioning
confidence: 99%
“…A quantitative description of the phosphine's stereoelectronic properties is most commonly provided by the Tolman electronic parameter (TEP) and cone angle . The classical boundaries of the electron‐releasing character of organophosphines have been recently expanded by Alcarazo's cationic phosphines that act as very strong π‐acceptor ligands, while Carrow et al showed that tri(1‐adamantyl)phosphine is significantly more donating than P( t Bu) 3 (Figure ) …”
Section: Figurementioning
confidence: 99%